Alpha lipoic acid: A therapeutic strategy that tend to limit the action of free radicals in transplantation - Ambrosi, Nella Gabriela (2018)
Organ replacement is an option to mitigate irreversible organ damage. This procedure has achieved a considerable degree of acceptance. However, several factors significantly limit its effectiveness. Among them, the initial inflammatory graft reaction due to ischemia-reperfusion injury (IRI) has a fundamental influence on the short and long term organ function. The reactive oxygen species (ROS) produced during the IRI actively participates in these adverse events. Therapeutic strategies that tend to limit the action of free radicals could result in beneficial effects in transplantation outcome. Accordingly, the anti-oxidant α-lipoic acid (ALA) have been proved to be protective in several animal experimental models and humans. In a clinical trial, ALA was found to decrease hepatic IRI after hepatic occlusion and resection. Furthermore, the treatment of cadaveric donor and recipient with ALA had a protective effect in the short-term outcome in simultaneous kidney and pancreas transplanted patients. These studies support ALA as a drug to mitigate the damage caused by IRI and reinforce the knowledge about the deleterious consequences of ROS on graft injury in transplantation. The goal of this review is to overview the current knowledge about ROS in transplantation and the use of ALA to mitigate it.